Human milk donation: difficulties and limiting factors - Larissa Santos Neves; Maria Vanessa Moreira Sá; Maria José Guardia Mattar; Mônica Santiago Galisa (O Mundo da Saúde, 2011)
Considering the benefits of maternal milk for children, Human Milk Banks (BLH) were created to guarantee the quality of human milk for premature newborns having low weight or hospitalized in Neonatal Intensive Care Units; they act with educative measures in order to contribute to the reduction of neonatal mortality. The objective of this study has been to identify limiting factors for the milk donation in the Human Milk Bank of the Hospital Maternidade Leonor Mendes de Barros [Hospital Maternity Leonor Mendes de Barros] and to sensitize milking mothers in the Joint Residence and pregnant women in prenatal period to become donors. The method of study was the prospective-transversal, which was done in the period of November 25 to December 2, 2009. Milking mothers in the Joint Residence and pregnant women in the prenatal period including donating ones have been interviewed and registered. The investigation used an individual interview with personal communication orb telephone, for answering referring questions of the elaborated protocol. Subjects were 81 pregnant women, 57 milking mothers and 7 donors, in a total of 145 women. Many of them already had heard about the Human Milk Bank, but no one knew the whole work carried out. The majority has said they would donate excess milk and half of the interviewed people had almost affirmed not to have difficulties for becoming donors; some of them have mentioned information deficiency. The profile of the possible milk donors has been identified, and we verified that many of them do not have knowledge on milk donation. We observed most women have no difficulty for donating; nevertheless, the number of donors is still small and the related difficulties may be solved with more spreading and elucidations on milk donation. The limiting factor found during this study was the lack of information and directions about human milk donation.